Training of Cadres and Volunteers to Support Tuberculosis Elimination in Kutalimbaru Village, Deliserdang Regency - Sianturi, Efendi; Surbakti, Elisabeth; Pardosi, Maida; Hutabarat, Julietta (Jurnal Pengabdian UNDIKMA, 2026)
This community service activity aims to improve the knowledge, attitudes, and practices of community health cadres and volunteers regarding tuberculosis (TB) prevention and control. The program involved 30 cadres and volunteers from Kutalimbaru Village, Deli Serdang Regency, North Sumatra, Indonesia, and was conducted at the Kutalimbaru Village Head’s Office. A Participatory Action Research (PAR) approach was employed through community engagement and participant recruitment, data collection and needs assessment, training sessions, distribution of TB educational pocketbooks, and evaluation using pre-test and post-test questionnaires. The data were analyzed descriptively using frequency and percentage distributions, and participants’ pre-test and post-test results were compared across knowledge, attitude, and practice categories. Before the intervention, the majority of participants demonstrated insufficient levels of knowledge (83.33%), attitudes (83.33%), and practices (80.00%). Following the intervention, 96.67% of participants achieved a good level of knowledge, while 93.33% attained good levels of attitudes and practices. The program also established the “Great Cadres and Volunteers, Together to Eliminate TB” group as community-based agents for TB education and support. Overall, the findings indicate that structured and interactive training supported by practical educational materials effectively strengthens the readiness of community health cadres and volunteers to provide TB education, encourage early case detection, promote treatment adherence, and reduce TB-related stigma within the community. Integrating trained cadres and volunteers into village health programs, supported by continuous mentoring and regular monitoring, has the potential to strengthen sustainable community-based TB prevention and control initiatives.